PELATIHAN PENTINGNYA PARENTING STYLE SEBAGAI UPAYA MEMBANGUN KARAKTER ANAK - idola perdana sulistyoning suharto; Endang Mei Yunalia; Satria Eureka Nurseskasatmata; Erik Irham Lutfi; Martianawati martianawati; Novia Ulfa; Fernando Fernando; Edwin Putra Setya Indiarto (Jurnal Abdi Masyarakat, 2021)
Children are the next generation of families and assets of the nation that must be prepared from an early age so that they become quality successors and have good character. Children's character is a container for various psychological characteristics that can guide children to adapt to various environmental conditions they face. The purpose of this activity is to increase parents' knowledge about Parenting Style as an Effort to Build Children's Character. The method used in this community service is Community Education (Counseling) through the Zoom Meeting media. Based on the results of the Wilcoxon Signed Rank test, it can be seen that the significance value (p value) is 0.00. The significance value is greater than Î± (0.05) so it can be interpreted that there is a significant difference in the knowledge of parents before and after counseling. Based on the results of this community service, it can be concluded that counseling to the community can increase parents' knowledge about Parenting Style as an Effort to Build Children's Character. Parents' knowledge about parenting needs to be improved, because knowledge about parenting will determine the type of parenting that will be given by parents to their children. So that the child will have a good character and in accordance with the norms of society